The Prevalence of High-Riding Jugular Bulb in Patients with Suspected Endolymphatic Hydrops - Brook, Christopher D.; Buch, Karen; Kaufmann, Matthew; Sakai, Osamu; Devaiah, Anand K. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Background To determine the prevalence of a high-riding jugular bulb (HRJB) in the endolymphatic hydrops population.Methods This was a retrospective chart and radiology review of patients seen at a tertiary care medical center. Patients were identified using the International Classification of Diseases, 9th edition, code 386.xx (Meniere disease–unspecified), and were required to have undergone an imaging study that included views of the jugular bulb that were available for review. A radiologist then evaluated all of the imaging studies for evidence of HRJB or inner ear dehiscence with a jugular bulb abnormality.Results The prevalence of a HRJB in all endolymphatic hydrops patients was 9.0% (7 of 78), and it was 4.5% (7 of 156) in all ears. The prevalence of HRJB ipsilateral to an ear with endolymphatic hydrops was 4.6% (4 of 88 ears); it was 4.4% (3 of 68 ears) in ears without endolymphatic hydrops. The incidence of inner ear dehiscence with a HRJB was 1.3% (1 of 78). Electrocochleography results were not correlated with jugular bulb volume.Discussion The results of this study indicate that a small subset of patients treated for endolymphatic hydrops patients have a HRJB. Overall, these results suggest that HRJB does not play a major role in endolymphatic hydrops, although it may play a role in a few isolated patients.
Keywords: Meniere disease; dizziness; lateral skull base; hearing loss